Making Benefit Sharing Arrangements Work for Forest-dependent Communities : Overview of Insights for REDD+ Initiatives - Chandrasekharan Behr, Diji (Program on Forests (PROFOR), Washington, DC, 2013)
This overview paper positions the question of benefit sharing in the context of REDD plus. It shares findings from a cursory review of a sample of Readiness Preparation Proposals (RPP) for REDD plus submitted to the Forest Carbon Partnership Facility (FCPF). It deconstructs the concept of benefit sharing. It also provides a summary of the main findings from three recent studies on benefit sharing that were financed by the Program on Forests (PROFOR). The PROFOR studies build on existing research. They also use primary and secondary data collected from a literature review, key informant interviews, structured surveys, and case studies. The studies: a) explore the substantive legal issues and procedural options for identifying legitimate and intended beneficiaries in situations where rights are unclear; b) provide information and tools to assist policy makers and development partners to design and develop nationally appropriate arrangements for transferring REDD plus benefits; and c) provide the local partners' perspective on benefit sharing and the process involved in determining benefits and establishing arrangements for sharing the benefits.